DEVELOPMENT OF ILLUSTRATION BOOK ON DENTAL AND ORAL HEALTHY IN CHILDREN (COMMUNITY EMPOWERMENT) - Robyana, Zhara; Chandra, Adellia Monica; Sinaredi, Betadion Rizki; Bramantoro, Taufan (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: Dental caries is a disease that affects all ages, including early childhood. According to the World Health Organization (WHO), the incidence of dental caries in Indonesian children aged 5 and 6 years in 2017-2018 reached 70% or more. Parental education in dental health from an early age plays a vital role. One of the easy-to-understand educational media is a picture book. Aim: This engagement activity was conducted to increase parental participation in the development of a picture book to meet the needs of dental health education for early childhood at Omah Cilik Fundaycare Surabaya Method: This activity was an online educational activity involving parents. It was a sharing session between participants and informants about early childhood dental and oral health problems. The increased participation of participants was assessed using a Google form when the activity was going on. Results: This activity revealed that 100% of participants were enthusiastic about getting the latest information about children's oral health, and more than 70% had the correct answers. Conclusion: Participants are quite enthusiastic and active during online discussions.